Russia and East Asia informal and gradual integration - Akaha, Tsuneo 1949-; Vassilieva, Anna (Abingdon, Oxon Routledge, 2014)
"Russia has generally been neglected in the academic and policy discourse on regional integration in East Asia. This book fills this gap, with particular attention to the role of Pacific Russia in the deepening regional integration in East Asia. It examines the increasingly diverse foreign policy interests of Russia related to emerging economic and political realities of the world, and Russia's potential role in the regional integration in East Asia. Topics discussed include Russian strategic interests and security policy in East Asia generally, Russia's bilateral relations with China, Japan, and the Korean Peninsula, opportunities and challenges energy and immigration presents for Russia and its engagement with East Asia, and Russia's present and future roles in regional integration in East Asia".
Introduction : Russia and East Asia / Tsuneo Akaha and Anna Vassilieva -- Russia's new global vision and security policy in East Asia / Vitaly Kozyrev -- Russia's security policy towards East Asia / Shinji Hyodo -- Russia's cconomic policy in East Asia / Pavel Minakir -- Russia-China relations / Natasha Kuhrt -- Japan's economic relations with the Russian Far East / Hiroshi Takahashi -- Russia and the Korean Peninsula / Beom-Shik Shin -- Russia and energy cooperation in East Asia / Kenji Horiuchi -- Russia's energy development in eastern Siberia and the Far East and relations with East Asian countries in the energy sector / Boris Saneev and Dmitry Sokolov -- Russia's immigration challenges / Zhanna Zaionchkovskaya, N.V. Mkrtchian, and E.V. Tyuryukanova -- Hot politics-cold economics and cold politics-hot economics : the limits of Russian, Chinese and Japanese "high politics" in view of East Asian integration / Christian Wirth -- Russia and regional integration in East Asia / Tsuneo Akaha and Anna Vassilieva.
Includes bibliographical references and index.
Keywords: National security -- Russia (Federation); Energy policy -- Russia (Federation); East Asian cooperation; SOCIAL SCIENCE / Ethnic Studies / General; East Asia -- Foreign relations -- Russia (Federation).; Russia (Federation) -- Foreign relations -- East Asia; East Asia -- Foreign economic relations -- Russia (Federation).; Russia (Federation) -- Foreign economic relations -- East Asia; East Asia -- Stategic aspects